1983
DOI: 10.1080/03079458308436169
|View full text |Cite
|
Sign up to set email alerts
|

Renal lesions in baby chicks due to sodium chloride poisoning

Abstract: SUMMARYThe pathogenesis is described of renal lesions which developed in 1-dayold chicks fed a ration containing 10% sodium chloride for 25 successive days. The gross lesions are described. Microscopically the kidneys showed that nephrosis and glomerular changes were very prominent. These included glomerular hypertrophy, formation of epithelial crescents, fibrous adhesions, lobularity, shrinkage and collapse of the glomerular tuft and thickening of the basement membrane of the capillary tuft. Segmental hyalino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…Similar results of enlarged kidneys in ascitic birds as a result of tubular and glomerular hypertrophy were previously reported (Sokkar et al, 1983;Maxwell et al, 1986;and Mirsalimi et al, 1993). Shrunken livers covered by a thin layer of semigelatinous material in ascites syndrome affected broilers were reported by Maxwell et al (1986).…”
Section: Discussionsupporting
confidence: 89%
“…Similar results of enlarged kidneys in ascitic birds as a result of tubular and glomerular hypertrophy were previously reported (Sokkar et al, 1983;Maxwell et al, 1986;and Mirsalimi et al, 1993). Shrunken livers covered by a thin layer of semigelatinous material in ascites syndrome affected broilers were reported by Maxwell et al (1986).…”
Section: Discussionsupporting
confidence: 89%
“…The lesions found in the kidney and liver are similar to those observed by Mohanty and West [14], Martindale [27], and Sokkar et al [28], who observed that the most affected tubules were the proximal tubules. The presence of mesangioproliferative glomerulopathy agrees with the reports of Puette et al [16] and Nishimura [29].…”
Section: Discussionsupporting
confidence: 87%
“…Most of the research on Na+ toxicity has been on the level required to cause disease and on the organs affected, mainly kidney, heart, brain and lung (Eleazer and Bierer, 1964;Krakower and Goettsch, 1945;Krakower and Heino, 1947;Mohanty and West, 1969;Paver et al, 1953;Sokkar et al, 1983). The mechanism of Na+ toxicity is rarely discussed.…”
Section: Discussionmentioning
confidence: 99%